Aportaciones al conocimiento de la flora gipsícola del Temple (Granada, España). Contributions to the knowledge of the gypsophilous flora of El Temple (Granada, Spain) - Fuentes Carretero, Julián Manuel (Acta Botanica Malacitana, 2013)
Contributions to the knowledge of the gypsophilous flora of El Temple (Granada, Spain) Palabras clave. Edafismo, gipsófito, gipsofilo, corología, Andalucía. Key words. Edaphism, gypsophyte, gysophile, chorology, Andalusia.